Youth Learning Opportunities and Digital Trends in Uganda - Muhereza M., Bob; Makumbi , Rita (African Journal of Education,Science and Technology (AJEST), 2022)
This study explores learning trends (formally and informally) as supported by digitalisation among the youth in Uganda. Over the years digitilisation has been incremental, and so has been a growing recruitment, exploration and encirclement towards the digital platforms as a medium of information delivery. The young people who are akin with these technologies have been brought together. The youth being the largest population in the country and naturally the most users of digital platforms, this has changed learning opportunities amongst this age bracket. The main objective of the study was to investigate the new trends of digital education among the youth in Uganda. The research design was a descriptive cross-sectional survey. The sample size consisted of 369 Ugandan youth. Simple random sampling was used to select various regions of the country, and systematic sampling was used to select respondents from the various strata. The link to the Google form was sent via email and WhatsApp Messenger to facilitate online sampling. The responses were coded, entered into IBM SPSS 26, and analysed to produce demographic and descriptive characteristics of the sample. Pearson’s correlation coefficient was used to establish the relationship between variables, and linear regression was used to determine the effect of the independent variable on the dependent variable. The findings show that learning technologies, such as print-material, radio, television, video, audio, mobile, computers, and the internet, offer a solution not only for resuming education where it has been disrupted, but also for overcoming geographical access and rigidity in traditional education. The study recommends that there is need for macro-based investments that will enhance increased digital learning.